Triatominae (Hemiptera: Reduviidae) fauna in bird nests: the case of Morrinhos, Ceara, Brazil - Santana, Jociel Klleyton Santos [UNESP]; Carneiro, Francisco Ronan; Alevi, Kaio Cesar Chaboli; Galvao, Cleber; Rosa, Joao Aristeu da [UNESP]; Oliveira, Jader de (Soc Vector Ecology, 2023)
Triatominae are associated with various Brazilian habitats, including bird nests, animal burrows, and peridomestic structures. Despite extensive studies on triatomines in domiciliary environments in Ceara, Brazil, there has been limited research on their presence in the wild. This study focuses on the municipality of Morrinhos in Ceara, which is characterized by a Caatinga biome and riparian forests along the Acarau River. During the study, a total of 185 nests ofPseudoseisura cristata were analyzed in rural locations and triatomines were collected in 26 nests from 12 different locations. A total of 117 triatomines was collected, belonging to three species: Psammolestes tertius, Rhodnius nasutus, and Triatoma pseudomaculata. Rhodnius nasutus was the only species found in a nest inhabited by Didelphis albiventris. Nests of P. cristata serve as shelters for various animals, providing an ideal environment for triatomines to establish colonies due to their proximity to food sources and their generalist feeding habits. The incorporation of anthropogenic materials by birds in nest construction can indirectly affect the presence of other animals that may serve as food sources for triatomines. Understanding the interactions between triatomines, birds, and their habitats is essential for assessing the risks associated with triatomine infestation in wild ecosystems. Journal of Vector Ecology 48 (2): 124-130. 2023.
Keywords: Vectors; Chagas disease; biodiversity; northeastern Brazil; kissing bug